Ginny walked into Math class and saw the following question on the board.

Find the value of the following expression when \begin{align*}a = -2, b = 3, c = -1, d = 1\end{align*}

\begin{align*}\boxed{(4a+c)\div b-(bd)\div (ac)}\end{align*}

Can you answer this question?

### Watch This

Khan Academy Order of Operations 1

Khan Academy More Complicated Order of Operations Example

### Guidance

The standard order of operations involves specific steps for performing the mathematical calculations presented in a mathematical statement. These steps are represented by the letters PEMDAS.

P – Parentheses – Do all the calculations within parentheses.

E – Exponents – Do all calculations that involve exponents.

M/D – Multiplication/Division – Do all multiplication and division, in the order it occurs, working from left to right.

A/S – Addition/Subtraction – Do all addition and subtraction, in the order it occurs, working from left to right.

These steps do not change whether they are being applied to positive real numbers or to negative real numbers. The rules for adding, subtracting, multiplying and dividing real negative numbers must be applied when evaluating expressions that require PEMDAS to be used.

#### Example A

Perform the following calculations: \begin{align*}32 \div 4^2 \times 2-21\end{align*}

**Solution:** There are no calculations inside parentheses. The first step is to evaluate the number with the exponent.

\begin{align*}=32\div {\color{blue}16}\times 2-21\end{align*}

The next step is to perform any division or multiplication, in the order they occur, working from left to right.

\begin{align*}={\color{blue}2} \times 2-21 \end{align*}

\begin{align*}={\color{blue}4}-21 \end{align*}

The final step is to rewrite the expression as an addition problem and to change the sign of the original number being subtracted.

\begin{align*}=4{\color{blue}+-}21 \end{align*}

When adding two numbers with unlike signs, subtract the numbers and the sign of the number with the greater magnitude will be the sign of the answer.

\begin{align*}= {\color{blue}-17}\end{align*}

#### Example B

Find the value of the following expression when \begin{align*}a = -2, b = 3, c = -1, d = 1\end{align*}

\begin{align*}(4a^2c^2)-(3ac^3)\end{align*}

**Solution:** Begin by substituting the variables with the given values. Use brackets to group the operations with parentheses.

\begin{align*}=[4(-2)^2(-1)^2] - [3(-2)(-1)^3]\end{align*}

In the first set of brackets, do the calculations with exponents.

\begin{align*}=[4({\color{blue}4})({\color{blue}1})] - [3(-2)(-1)^3] \end{align*}

In the second set of brackets, do the calculations with exponents.

\begin{align*}=[4(4)(1)]-[3(-2)({\color{blue}-1})] \end{align*}

In the first set of brackets, do the multiplication. The brackets can now be removed.

\begin{align*}={\color{blue}16}-[3(-2)({\color{blue}-1})] \end{align*}

In the second set of brackets, do the multiplication. The brackets can now be removed.

\begin{align*}=16-{\color{blue}6} \end{align*}

Subtract the numbers.

\begin{align*}={\color{blue}10}\end{align*}

#### Example C

What is the value of \begin{align*}3-2 \left[\frac{8(-1)-7}{-3(2)-4}\right]\end{align*}

**Solution:** =\begin{align*}3-2\left[\frac{{\color{blue}-8}-7}{-3(2)-4}\right] \end{align*}

\begin{align*}=3-2\left[\frac{-8-7}{{\color{blue}-6}-4}\right]\end{align*}

\begin{align*}=3-2 \left[\frac{-8{\color{blue}+-}7}{-6{\color{blue}+-}4}\right] \end{align*}

\begin{align*}=3-2\left[{\color{blue}\frac{-15}{-10}}\right] \end{align*}

\begin{align*}=3- {\color{blue}\frac{-30}{-10}} \end{align*}

\begin{align*}=3-{\color{blue}3} \end{align*}

\begin{align*}={\color{blue}0}\end{align*}

#### Concept Problem Revisited

Find the value of the following expression when \begin{align*}a = -2, b = 3, c = -1, d = 1\end{align*}

\begin{align*}\boxed{(4a+c)\div b-(bd)\div (ac)}\end{align*}

Ginny felt good about answering the problem because she remembered the steps involved in the standard order of operations. When she noticed that the values for two of the variables were negative numbers, she realized that she would have to be careful doing the calculations because she would also have to apply the rules that she had learned for adding, subtracting, multiplying and dividing negative real numbers.

\begin{align*}(4a+c)\div b-(bd) \div(ac)\end{align*}

Ginny began by substituting the variables with the given values.

\begin{align*}(4(-2)+(-1))\div 3-((3)(1))\div((-2)(-1))\end{align*}

To reduce errors in her calculations, Ginny wrote all of the values in parentheses. The statement now has parentheses within parentheses. This may seem confusing and the order in which to perform the operations may become skewed. Ginny asked her teacher about writing the expression another way. Her teacher advised her to replace the outer parentheses with brackets [ ]. Brackets are another type of grouping symbol. When evaluating an expression that has grouping symbols (parentheses) within grouping symbols (brackets), perform the operations within the innermost set of symbols first. This is not necessary, but it is a good rule to follow.

Ginny rewrote the expression using both brackets and parentheses.

\begin{align*}[4(-2)+(-1)]\div 3-[(3)(1)] \div [(-2)(-1)]\end{align*}

\begin{align*}=[{\color{blue}-8}+(-1)]\div 3 - [(3)(1)] \div [(-2)(-1)]\end{align*}

\begin{align*}=[-8+(-1)] \div 3-[3]\div[2]\end{align*}

\begin{align*}=[{\color{blue}-9}] \div 3-[3] \div [2]\end{align*}

\begin{align*}=-9\div 3-3\div 2\end{align*}

\begin{align*}={\color{blue}-3}-3 \div 2\end{align*}

\begin{align*}=-3- 1.5\end{align*}

\begin{align*}=-3- 1.5 \rightarrow -3+ -1.5\end{align*}

\begin{align*}=-3+ -1.5\end{align*}

\begin{align*}={\color{blue}-4.5}\end{align*}

### Guided Practice

1. Perform the following operations: \begin{align*}8 \times -9 +19 \div (-30+11)-14 \times (-1)^2\end{align*}

2. Determine the answer to: \begin{align*}\left(\frac{-12-6}{6+3}\right)+\left(\frac{-36}{-4}\right)+(-8 \times 2)\end{align*}

3. A formula from geometry is \begin{align*}V=\frac{h}{6}(B+4M+b)\end{align*}. Find \begin{align*}V\end{align*} when \begin{align*}h = -15, B = 12,M = 8, b = 4\end{align*}.

**Answers:**

1.

\begin{align*} & 8 \times -9+19 \div (-30+11)-14 \times (-1)^2\\ & =8 \times 9 +19 \div {\color{blue}-19}-14 \times (-1)^2 \\ & =8 \times9+19 \div {\color{blue}-19}-14 \times (-1)^2 \\ & ={\color{blue}72}+19 \div -19-14\times 1\\ & =72+{\color{blue}-1}-14 \times 1 \\ & =72+-1-{\color{blue}14} \\ & ={\color{blue}71}-14 \\ & ={\color{blue}57}\end{align*}

2.

\begin{align*}& \left(\frac{-12-6}{6+3}\right)+\left(\frac{-36}{-4}\right)+(-8 \times 2)\\ & =\left({\color{blue}\frac{-18}{9}}\right)+\left(\frac{-36}{-4}\right)+(-8 \times 2)\\ & ={\color{blue}-2}+\left(\frac{-36}{-4}\right)+(-8 \times 2)\\ & =-2+{\color{blue}9}+(-8 \times 2)\\ & =-2+9+{\color{blue}-16}\\ & ={\color{blue}-9}\end{align*}

3.

\begin{align*}& V=\frac{h}{6}(B+4M+b).\\ & V=\frac{-15}{6}(12+4(8)+4)\\ & V=\frac{-15}{6}(12+{\color{blue}32}+4)\\ & V=\frac{-15}{6}(\color{blue}48)\\ & V={\color{blue}-2.5}(48)\\ & V={\color{blue}-120}\end{align*}

### Explore More

- If \begin{align*}a = -3, b = 1\end{align*} and \begin{align*}c = 2\end{align*}, what is the value of \begin{align*}2a^3-3b+2c^2\end{align*}? _______
- 221
- 59
- –49
- 43

- Evaluate \begin{align*}a-bc\end{align*} when \begin{align*}a=\frac{1}{2}, b=\frac{1}{3}\end{align*} and \begin{align*}c=\frac{5}{4}\end{align*}: _______
- 1
- \begin{align*}\frac{1}{12}\end{align*}
- \begin{align*}\frac{2}{5}\end{align*}
- \begin{align*}\frac{5}{2}\end{align*}

- Evaluate: \begin{align*}a(-b^2-a^2)\end{align*} when \begin{align*}a=-3\end{align*} and \begin{align*}b=4\end{align*} _______
- 75
- 2
- 3
- 4

- Simplify the following: \begin{align*}[3-[5-(6-8)]+4]-2\end{align*} _______
- –6
- –2
- 2
- –19

- Perform the following operations and evaluate: \begin{align*}(5\times 3-7)^2 \div 4+9\end{align*} _______
- 109
- 5
- 11
- 25

- Which expression has the greatest value if \begin{align*}a=-2\end{align*} and \begin{align*}b=3\end{align*}?
- \begin{align*}3[a^2+b^2-2ab-2(a^2-b^2)]\end{align*}
- \begin{align*} 3(a-b)-2(b-a)+3(a-2b)\end{align*}
- \begin{align*} b(a-b)-a(b-a)-ab\end{align*}

Perform the indicated calculations.

- \begin{align*}\frac{6-(24-14)}{-10-[2-(-4)^2]}\end{align*}
- \begin{align*}\frac{[12-(-15+6)]\times 4 -16}{-4}\end{align*}
- \begin{align*}3\left(-2 \times \frac{20}{-4 \times -1}-5-7\right)\end{align*}
- \begin{align*}-3 \times 5 -[3(3+9)-9\times -3]\end{align*}
- \begin{align*}4^2-(4+8-2-4-2\times 7)\end{align*}
- \begin{align*}2\times -18+9\div -3-5\times -2\end{align*}
- \begin{align*}-4\times (-12-8)\div -2\end{align*}
- \begin{align*}-15-6\div 3\end{align*}
- \begin{align*}\frac{-2-(15-5)}{-4\times -2-12+-6\div 3}\end{align*}